The gender pay gap in women's football: an analysis within the Ecuadorian legal framework (Revista científica Olimpia, 2026)
The gender pay gap in women's football is evident in Ecuador, with significant differences in compensation between male and female football players. This phenomenon reflects economic inequality within the sports sector, expressed in basic salaries as well as in bonuses, sponsorships, and other forms of compensation. The purpose of this research is to thoroughly analyze the factors and circumstances that influence the working conditions of female players, as well as to examine current legislation, in order to identify areas that need improvement to enhance these conditions. The main goal is for female football players to be able to live off and rely on their profession under equal opportunities compared to their male counterparts. The research was conducted using a qualitative approach, with a review of national and international regulations, comparative analysis, and the study of relevant cases. Although there are no specific statistical data on Ecuadorian women's football, the general context reveals a significant gap. In Ecuador, the need to recognize and remunerate female sports professionals equally under the law is evident, but it is still under development. Current regulations provide applicable tools, although there are still shortcomings in mechanisms, concrete data, and sports policies aimed at ensuring pay equity.
Keywords: wage gap, women's football, legal framework, gender equality